2022
DOI: 10.1080/00313831.2022.2042850
|View full text |Cite
|
Sign up to set email alerts
|

Playful Learning During the Reopening of Danish Schools After Covid 19 Closures

Abstract: This article is based on qualitative and quantitative data collected from teachers and pupils in Danish schools in June 2020, as schools reopened following closures in the spring due to the COVID-19 pandemic. It investigates the transformations in school life that took place in this period in response to strict official guidelines to prevent the spread of infection, transformations both in school learning environments and in teaching activities. Using factor and cluster analyses and logistic regression, it exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…12 In a sample of 174 teachers in Denmark, 43% of the participants reported that they felt nervous or anxious due to the COVID-19 outbreak. 13 In our sample, the prevalence of individuals reporting fear of infection or fear of transmitting infection from work to home, was similar to what we have observed among employees working within eldercare, childcare and hospital/ rehabilitation, respectively. 14 The prevalence of teachers, who feared transmitting infection to pupils, was comparable to the figures for employees in childcare, and lower than observed among employees in eldercare.…”
Section: Main Findings and Comparison With Previous Researchsupporting
confidence: 87%
See 1 more Smart Citation
“…12 In a sample of 174 teachers in Denmark, 43% of the participants reported that they felt nervous or anxious due to the COVID-19 outbreak. 13 In our sample, the prevalence of individuals reporting fear of infection or fear of transmitting infection from work to home, was similar to what we have observed among employees working within eldercare, childcare and hospital/ rehabilitation, respectively. 14 The prevalence of teachers, who feared transmitting infection to pupils, was comparable to the figures for employees in childcare, and lower than observed among employees in eldercare.…”
Section: Main Findings and Comparison With Previous Researchsupporting
confidence: 87%
“…Not surprisingly, another qualitative study including 8 teachers of children with special needs, that is, refugees, found it particularly challenging to support their pupils during the school closure 12 . In a sample of 174 teachers in Denmark, 43% of the participants reported that they felt nervous or anxious due to the COVID-19 outbreak 13 . In our sample, the prevalence of individuals reporting fear of infection or fear of transmitting infection from work to home, was similar to what we have observed among employees working within eldercare, childcare and hospital/rehabilitation, respectively 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in a different context (Denmark) showed that in a sample of 174 teachers, 43% of participants reported feeling nervous or anxious about the outbreak of COVID-19 [11]. In this study, most reported fear of infection or fear of transmitting the infection from work to home, the same as employees working in elder care, child-care, hospitals and rehabilitation facilities [12]. Several studies [13,14] have shown that one of the main causes of healthcare workers' fears during the pandemic was the fear of infecting family members, which was even greater than the fear of infecting themselves.…”
Section: Introductionmentioning
confidence: 47%
“…As students progress, they seem to exhibit greater independence from state factors in their academic well-being, while simultaneously becoming more state reliant in their social well-being. It is shown that academic well-being is correlated with students' perceived coping, i.e., their perceived ability to cope with activities or tasks they are faced with in specific contexts [68], and that repeated experiences of perceived coping or lack of perceived coping will affect the more context-independent self-efficacy or belief in own abilities [69]. Therefore, it is-especially in the period when academic well-being is state reliant-important to support the students' perceived coping.…”
Section: State And/or Trait Dependent Well-being Fluctuationsmentioning
confidence: 99%
“…There are several ways to do this, but for example positive feedback is important. Furthermore, during the COVID19-period, studies found that student-centered activities, such as guided discovery, project oriented, problem-based, and inquiry-based activities, positively affected students' social and academic well-being [68].…”
Section: State And/or Trait Dependent Well-being Fluctuationsmentioning
confidence: 99%